24h SCAI stage reclassification to predict outcome. Insights from the prospective Altshock-2 registry. (3rd October 2022) - Morici, N; Frea, S; Ditali, V; Briani, M; Bertaina, M; Ravera, A; Sorini Dini, C; Moltrasio, M; Saia, F; Corrada, E; De Ferrari, G M; Garatti, L; et al.
Abstract: Background: Cardiogenic shock (CS) includes several phenotypes of congestion or hypoperfusion with heterogenous hemodynamic features. Timely prognostication with scoring tools is warranted to identify patients requiring escalation to mechanical circulatory support (MCS) and to avoid futility. Purpose: Accordingly, we explored the role of the updated Society for Cardiovascular Angiography and Interventions (SCAI) stages classification on in-hospital mortality using a prospective national registry. Methods: The Altshock-2 Registry includes 237 patients with CS of all etiologies enrolled between March 2020 and February 2022 in 11 Italian Centers. Patients were classified according to the admission SCAI stages (assigned prospectively and independently updated according to the most recently released version); 24-hour re-assessment was prospectively performed in 201 patients. In-hospital mortality was evaluated for association with admission and 24 hours SCAI stages adjusted for the most relevant clinical covariates. Results: Of the 237 patients included, 20 (8.4%) had SCAI shock stage B, 132 (55.8%) SCAI stage C, 60 (25.3) SCAI stage D and 25 (10.5%) SCAI stage E. Patients in stage B had the worst reclassification at 24-hours, with 42% of them showing worsened status and only 8% improving. In-hospital mortality was 38%. The revised SCAI stages at baseline were not independently associated with in-hospital mortality, whereas the SCAI classification at 24-h correctly and independently predicted mortality (the rate of in-hospital death was 18% for patients in SCAI shock stage B, 27% for SCAI shock stage C, 64% for SCAI shock stage D, 100% for SCAI shock stage E). At the multivariate analysis (adjusted for age, gender, eGFR, inotropic score and MCS) only SCAI classification at 24-hour evaluation was an independent predictor of in-hospital mortality (OR and 95% CI were, respectively, 3.32, 0.36–30.63, p=0.290 for SCAI stage C and 13.07, 1.69–146.3 for SCAI stage D, with E perfectly predicting because all patients died). Conclusions: The revised SCAI stage classification may improve prognostication only at 24-hour evaluation. Aggressive treatment (either pharmacological or with MCS escalation) should be tailored in order to achieve prompt clinical improvement within the first 24-hours; refractory SCAI stage E at 24 hours portends dismal prognosis. Funding Acknowledgement: Type of funding sources: None.